A design of Automatic UAV Dock Platform System. Issue 2 (October 2020) - Zang, Zhibin; Ma, Jun; Li, Chaoyang; Wang, Haoran; Jing, Ruirui; Shi, Yongxiang
Abstract: At present, most unmanned aerial vehicles (UAVs) are powered by traditional aero modelling lithium batteries, which have poor endurance and cannot operate continuously for a long time. It greatly limits the application fields of UAVs. To tackle this problem, we design a fully-automatic UAV docking platform that can work under no human situation and assistance to charge the aircraft with insufficient power to help the drone extend its battery life. It also provides an implementation solution for a fully automatic drone docking platform with wireless charging, UAV takeoff and returns, auxiliary positioning, and relay communication. The system mainly includes apron part, docking platform protective shell, solar panel, power conversion equipment, wireless charging base, satellite positioning and communication module, radio positioning signal generator, and radio relay communication module, etc. The power system of the apron part uses electric pushrods.